The Triviality of Measuring Ultimate Outcomes: Acknowledging the Span of Direct Influence. (November 2014) - Ton, Giel; Vellema, Sietze; Ge, Lan
Abstract Sustainability standards and certification schemes have been promoted as a market‐driven instrument for realising development impacts and receive public funding. As a result, companies, NGOs and supporting donors and governments want to know if these ambitions have been fulfilled. Their tendency is to commission household surveys to assess net effects of certification in areas such as poverty, productivity and food security. This article argues that, rather than trying to measure precise net effects on farmer income, the focus should be on detailed measurement of more immediate outcomes in terms of knowledge and implementation of good agricultural practices. Contribution analysis is proposed as an overall approach to verify the theory of change, combining survey‐based net‐effect measurement of these immediate and intermediate outcomes with less precise, lean monitoring of indicators to verify the contributory role of these outcomes that are outside the span of direct influence, such as household income and poverty alleviation.